Heterotic responses of tetraploid and triploid plantain hybrids in southeast Nigeria - Wilson, V.; Tenkouano, A.; Pasberg-Gauhl, C.; Gauhl, F. (1999)
Genetic enhancement of plantain (Musa spp. L., AAB group) has aimed at producing hybrids with high yield, short stature, early maturity, fast crop cycling, and disease resistance. Two tetraploid clones derived from the plantain landrace ‘Bobby Tannap’ (BT) and ‘Obino l’Ewai’ (OL) were crossed to a diploid clone to produce two triploid hybrids. These materials were evaluated for resistance to black sigatoka, yield potential and growth habit. Compared to the landraces, disease progress was delayed in both tetraploid (>80 days) and triploid progenies (70-80 days) and necrotic area was less. Tetraploid hybrids maintained a large number of photosynthetically- active leaves than the triploid hybrids and the plaintain landraces. High parent heterosis for bunch weight was achieved in the triploid hybrid of BT (+17%), but notin the OL- triploid hybid (-28%).